COVID-19 Pandemic—What Should Not Be Forgotten - Koechlin, Luca (The Thoracic and Cardiovascular Surgeon Reports, 2021)
The Swiss Society of Cardiac Surgery (SGHC) has announced a “Special Swiss Young Cardiac Surgeon Award 2020,” with the aim to learn more about the consequences of the coronavirus disease 2019 (COVID-19) pandemic for young Swiss cardiac surgeons. Therefore, the overall goal of this article is to highlight the personal situation and perspective of a young Swiss cardiac surgeon in training during the COVID-19 pandemic. This article reflects the personal opinion of a young Swiss cardiac surgeon discussing the impact of the pandemic for young surgeons in training and potential chances and learning effects.
Keywords: cardiac; cardiovascular surgery; education; level